2021
DOI: 10.1111/1753-6405.13158
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health service adaptations to the coronavirus disease 2019 (COVID‐19) pandemic in Australia: a nationwide online survey

Abstract: Objective: Examine the changes in service delivery Australian public sexual health clinics made to remain open during lockdown. Methods: A cross‐sectional survey designed and delivered on Qualtrics was emailed to 21 directors of public sexual health clinics across Australia from July‐August 2020 and asked about a variety of changes to service delivery. Descriptive statistics were calculated. Results: Twenty clinics participated, all remained open and reported service changes, including suspension of walk‐in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
(28 reference statements)
1
23
0
1
Order By: Relevance
“…The number of male sex partners, recent HIV testing and PrEP use all fell substantially after COVID-19 emerged, although longer-term trends in these indicators appeared unaffected after adjusting for variations in sampling. HIV treatment and viral suppression were sustained at high levels, and did not seem to be affected by COVID-19, reflecting the quick response of HIV-positive people and clinical services to sustain access to treatment, such as using telehealth consultations [ 41 ]. Although the overall proportion of GBM reporting casual sex fell after COVID-19, among those who continued to have casual sex, the proportion reporting condomless sex with a risk of HIV transmission increased, linked to the drop in PrEP coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The number of male sex partners, recent HIV testing and PrEP use all fell substantially after COVID-19 emerged, although longer-term trends in these indicators appeared unaffected after adjusting for variations in sampling. HIV treatment and viral suppression were sustained at high levels, and did not seem to be affected by COVID-19, reflecting the quick response of HIV-positive people and clinical services to sustain access to treatment, such as using telehealth consultations [ 41 ]. Although the overall proportion of GBM reporting casual sex fell after COVID-19, among those who continued to have casual sex, the proportion reporting condomless sex with a risk of HIV transmission increased, linked to the drop in PrEP coverage.…”
Section: Discussionmentioning
confidence: 99%
“…These disruptions may be due to the different lockdown measures and restrictions in different settings, including the closure of public transport, restrictions on private vehicles' movement, closure of sexual health services, and suspension of non-emergency services during the lockdown periods, which may have impacted individuals access to 9 of 12 HIV testing [18,[22][23][24]. However, the reductions in HIV testing in our study were likely due to the changes in individuals' behaviours or attitudes instead of structural disruptions, because Australian sexual health clinics remained open and provided HIV/STI services during the lockdown periods [25]. As the COVID-19 pandemic continues, an alternative approach to scaling up HIV testing would be required.…”
Section: Discussionmentioning
confidence: 82%
“…Our data were collected before the start of the COVID-19 pandemic (the first Australian cases of COVID-19 were identified in January 2020), and therefore, we are unable to comment on any changes in sexual practices among heterosexuals due to the pandemic. However, previous studies have shown that there was a reduction in self-reported sexual activities and asymptomatic HIV/STI screening in heterosexuals during the COVID-19 pandemic in Australia [ 34 , 35 , 36 ]. Ongoing behavioural surveillance is warranted among heterosexuals in order to understand STI and HIV risk and to inform best clinical practice.…”
Section: Discussionmentioning
confidence: 99%